Collapse. Institutional Decline and Breakdown, Its Endogeneity and Its Asymmetry Vis-á-Vis Emergence: A Theoretical Frame. Issue 1 (2nd January 2021) - Elsner, Wolfram
Abstract: Collapse is considered a breakup of institutions and entire socio-economies. Collapse has accompanied socio-economic history, but seems to have become more topical again in recent decades. We even face the danger of extinction of the human species, due to anthropocenic climate change, not the least based on failure of institutional arrangements. Uprooting migration and "failing states" have become topical as well. Mainstream economics seems to have no clue about all that, advising ever more good old "market-economy institutions." Evolutionary and institutional economics has focused on institutional emergence, evolution, and persistent structures, but still not so much on decline and collapse. I develop an endogenous explanation of institutional decline and collapse implied by the previous success of institutionalized cooperation and increasing (over-)complexity, which exceeds individual cognitive capacities. Institutional adaptability and problem-solving capacity then decline. Uneven distribution of cooperation gains will further cause social conflict and institutional ceremonialization, decline, and collapse. Collapse will not just be a symmetric reverse of emergence. Being subject to sunk costs during emergence, to habituation and normativation, institutions tend to display some hysteresis. The article adopts an evolutionary-institutional perspective, in order to conceptualize future modeling.